2018
DOI: 10.1016/j.jacbts.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Infusion of the Novel HNO Donor BMS-986231 Is Associated With Beneficial Inotropic, Lusitropic, and Vasodilatory Properties in 2 Canine Models of Heart Failure

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
2
14
0
2
Order By: Relevance
“…Nitroxyl donors release HNO via chemical breakdown upon exposure to the physiological aqueous environment. In large animal models of HF, HNO donors directly enhance both contractility and relaxation and reduce both preload and afterload . Despite reliable augmentation of inotropy and lusitropy in these models, HNO donors do not increase heart rate or myocardial oxygen consumption, nor do they result in QT prolongation .…”
Section: Rationale For Nitroxyl Therapy In Heart Failurementioning
confidence: 98%
See 1 more Smart Citation
“…Nitroxyl donors release HNO via chemical breakdown upon exposure to the physiological aqueous environment. In large animal models of HF, HNO donors directly enhance both contractility and relaxation and reduce both preload and afterload . Despite reliable augmentation of inotropy and lusitropy in these models, HNO donors do not increase heart rate or myocardial oxygen consumption, nor do they result in QT prolongation .…”
Section: Rationale For Nitroxyl Therapy In Heart Failurementioning
confidence: 98%
“…In large animal models of HF, HNO donors directly enhance both contractility and relaxation and reduce both preload and afterload . Despite reliable augmentation of inotropy and lusitropy in these models, HNO donors do not increase heart rate or myocardial oxygen consumption, nor do they result in QT prolongation . This combination of physiological effects makes HNO donors potentially attractive therapeutic candidates in HF.…”
Section: Rationale For Nitroxyl Therapy In Heart Failurementioning
confidence: 99%
“…BMS‐986231 is a novel HNO donor that induces positive inotropy and lusitropy, along with vasodilatory effects, through mechanisms distinct from any currently available HF therapies . Animal HF models have demonstrated that BMS‐986231 reduces peripheral resistance and enhances cardiac contractility without increasing myocardial oxygen consumption, heart rate, or risk of arrhythmias …”
Section: Discussionmentioning
confidence: 99%
“…BMS‐986231 (formerly CXL‐1427), a novel second‐generation HNO donor, delivers HNO via pH‐dependent chemical breakdown when exposed to the neutral pH environment of the bloodstream. Increasing BMS‐986231 dose infusions in dogs with induced cardiomyopathy resulted in reductions in mean arterial pressure, systemic vascular resistance, Tau, and the end‐diastolic pressure volume relationship; increased left ventricular ejection fraction/fractional area shortening, end‐systolic pressure volume, and preload‐recruitable stroke work relationship parameters were also noted . These findings suggest that BMS‐986231 possesses positive lusitropic and inotropic as well as vasodilatory effects.…”
mentioning
confidence: 81%
See 1 more Smart Citation